Profile of Erythrocyte Index Values in Patients with Pulmonary Tuberculosis at Bendan Regional Hospital, Pekalongan City - Qomariyah, Ismi Tri; Wibowo, Subur (INDOGENIUS, 2025)
Background & Objective: Pulmonary tuberculosis (commonly known as TB) is an infectious disease caused by Mycobacterium tuberculosis. If not treated properly, this disease has the potential to cause various serious complications, even death. The objective of this study was to describe the erythrocyte index values in patients with pulmonary tuberculosis at Bendan Regional Hospital, Pekalongan City. Method: This research used a descriptive approach involving 30 samples. Examination of erythrocyte indices was carried out using an automatic analyzer method. Result: The results showed that 13 samples (43%) had microcytic hypochromic anemia, 9 samples (30%) had normocytic normochromic anemia, 5 samples (17%) had microcytic normochromic anemia, and 3 samples (10%) had normocytic hypochromic anemia. Conclusion: Overall, the most common type of anemia found in TB patients at Bendan Regional Hospital, Pekalongan City was microcytic hypochromic anemia.